A method for preparing a complex isomerization agent for regenerating complex isomerization of class I base oil to produce class II base oil
Patent Information
- Application Number
- CN202611394279.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-09
- Publication Date
- 2026-10-16
AI Technical Summary
[0008]本发明的目的之一在于提供一种用于再生Ⅰ类基础油络合异构生产Ⅱ类基础油的络合异构剂制备方法,解决现有络合异构剂快速失活的问题
(1)稀盐酸预酸化表层活化,为外壳沉积提供锚定基础。采用质量浓度8%~15%的稀盐酸在60℃~80℃下对200~400目膨润土进行1~3小时轻度预酸化,固液质量比控制在1:(3~5),该条件下酸液仅溶蚀颗粒表层,产生大量表面硅羟基(Si-OH)作为后续铝氧层沉积的化学键合位点,同时保持内部蒙脱石晶格基本完整,避免铝离子在后续沉积步骤中渗入内核破坏梯度结构。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lubricating oil base oil processing technology, specifically relating to a method for preparing a complexing isomer for the production of Group II base oils by complexing isomerization of regenerated Group I base oils. Background Technology
[0002] Lubricating oil base oils are the fundamental components of lubricating oil products, accounting for 70% to 95% of the total volume. According to the API classification standard, Group I base oils are produced using traditional solvent refining processes, with a saturated hydrocarbon content of less than 90%; Group II base oils are produced using hydrogenation processes, with a saturated hydrocarbon content greater than 90% and a sulfur content of less than 0.03%, exhibiting superior oxidation stability and low-temperature performance. With the upgrading of lubricating oil quality, the demand for Group II and above base oils continues to grow.
[0003] my country generates a large amount of waste lubricating oil annually. Regenerated Group I base oils can be obtained through regeneration processes, but due to technological bottlenecks, recycled oils generally suffer from problems such as high aromatic content, NMP solvent residue, high asphaltenes and gum content, and low viscosity index, making it difficult to directly meet Group II standards. Current upgrade routes mainly rely on hydroisomerization dewaxing, such as the hydrotreating-catalytic dewaxing-hydrorefining process disclosed in CN108473881A. However, this involves large equipment investments and high operating costs, making it unaffordable for small and medium-sized enterprises.
[0004] Acidified bentonite (activated clay) is a commonly used adsorption and purification material, produced by treating natural bentonite with inorganic acids. It possesses certain acidity and adsorption properties. In existing technologies such as CN104830515A, activated clay is only used as a physical adsorbent for decolorization and impurity removal, and cannot achieve aromatic isomerization conversion. Although ordinary acidified bentonite contains Brønsted acid (B acid) and Lewis acid (L acid) sites, the acid content is insufficient and the distribution is disordered, resulting in limited catalytic activity.
[0005] To improve the performance of acidified bentonite, existing technologies often employ single-acid (hydrochloric acid or sulfuric acid) modification, or optimize it through metal ion impregnation, organic modification, etc. However, single-acid modification has inherent drawbacks: hydrochloric acid acidification offers a large specific surface area but insufficient acid strength, while sulfuric acid acidification provides high acid content but easily causes pore collapse. Although metal impregnation can increase L-acid sites, the impregnated metal is prone to agglomeration and loss, and the spatially random distribution of Brønsted (B) and L-acids prevents the full realization of their synergistic effect.
[0006] A more critical technical problem is that the regenerated Group I base oil contains a large number of large-molecule polar impurities such as gums and asphaltenes. These impurities have large molecular sizes and are easily adsorbed and accumulated at the pore openings of the catalyst, causing pore blockage. This prevents the internal active sites from contacting the reactants, resulting in a rapid decline in catalyst activity after long-term operation, short service life, and frequent regeneration.
[0007] Therefore, developing a novel complexing isomer that can structurally solve the problem of impurity blockage is of great significance for promoting the upgrading of waste lubricating oil regeneration base oil. Summary of the Invention
[0008] One of the objectives of this invention is to provide a method for preparing a complexing isomer for the production of Group II base oils by complexing isomerization of regenerated Group I base oils, thereby solving the problem of rapid deactivation of existing complexing isomers.
[0009] The objective of this invention can be achieved through the following technical solutions: A method for preparing a complexing isomer for the complexation isomerization of regenerated Group I base oils to produce Group II base oils includes the following steps: (1) Pre-acidification treatment: The bentonite raw material is crushed to 200-400 mesh, added to dilute hydrochloric acid with a mass concentration of 8%-15%, with a solid-liquid mass ratio of 1:(3-5), and stirred at 60℃-80℃ for 1-3 hours. After filtration and washing, pre-acidified bentonite powder is obtained. (2) In-situ deposition of aluminum oxide shell: The pre-acidified bentonite powder is dispersed in deionized water to prepare a suspension with a mass fraction of 5% to 10%. Aluminum salt and urea are added, and the temperature is raised to 90℃ to 98℃ to carry out a homogeneous hydrolysis reaction of urea for 4 to 8 hours. A thin layer of aluminum oxide hydrate is deposited in-situ on the surface of bentonite particles to obtain core-shell precursor slurry. (3) Deep acidification with mixed acid: Hydrochloric acid and sulfuric acid are added to the core-shell precursor slurry, and the volume ratio of hydrochloric acid to sulfuric acid in the system is adjusted to (1~3):1. The total mass concentration of mixed acid is 25%~35%. Deep acidification reaction is carried out at 100℃~120℃ for 4~8 hours to obtain acidified slurry. (4) Hydrothermal setting and post-treatment: The acidified slurry is transferred to a hydrothermal reactor and hydrothermally treated at 140℃~160℃ for 2~4 hours. After cooling, the solid and liquid are separated, the solid product is collected, washed until neutral and then dried to obtain the complexing isomer. The complexing isomer has a core-shell gradient structure. The core is a deeply acidified bentonite rich in Brønsted acid centers for catalyzing the hydroisomerization of aromatics to produce saturated cycloalkanes. The outer shell is an aluminum-oxygen modified layer rich in Lewis acid, with aluminum elements distributed in a gradient decreasing from the surface to the inside, for coordination complexation and adsorption of polar impurities such as N-methylpyrrolidone, gums, and asphaltenes.
[0010] Mild pre-acidification with dilute hydrochloric acid only dissolves the surface layer of the particles, generating silanol groups while maintaining the integrity of the internal crystal lattice. This provides chemical bonding anchors for the subsequent alumina layer and prevents aluminum ions from penetrating into the core. Homogeneous hydrolysis of urea slowly releases OH-. - , making Al 3+ A gradient-distributed aluminum oxide thin layer is uniformly deposited on the surface, and this layer is rich in coordinate-unsaturated Al. 3+Lewis acids, also known as mixed acids, can preferentially complex polar impurities containing lone pairs of electrons, such as NMP and colloids, through coordination; deep acidification of mixed acids can displace H from internally activated montmorillonite octahedral sheets. + Brønsted acid centers are formed, and the aluminum oxide layer is etched out to expose more unsaturated sites; hydrothermal conditions promote the dehydration condensation of Si-OH and Al-OH at the interface to form Si-O-Al bonds, which fix the core-shell structure.
[0011] Furthermore, in step (2), the aluminum salt is aluminum nitrate nonahydrate or aluminum sulfate octadecahydrate, and the amount of aluminum salt added is 3% to 8% of the bentonite mass based on Al2O3; the molar ratio of urea to aluminum salt is (5 to 10): 1. Both aluminum nitrate and aluminum sulfate are soluble aluminum salts, and the anions do not introduce impurities; the 3% to 8% Al2O3 loading is appropriate for the shell thickness, below 3% the impurity interception is insufficient, and above 8% the pores are covered, increasing the mass transfer resistance; urea, as a homogeneous precipitant, has a moderate hydrolysis rate when the molar ratio is 5 to 10 times that of aluminum salt, which can ensure uniform deposition of the aluminum oxide layer without agglomeration.
[0012] Furthermore, in step (3), the volume ratio of hydrochloric acid to sulfuric acid is (1.5-2.5):1, and the total mass concentration of the mixed acid is 28%-32%; the deep acidification reaction temperature is 105℃-115℃, and the reaction time is 5-7 hours; the total solid-liquid mass ratio of the system after acid replenishment is 1:(4-8). Hydrochloric acid acidification is beneficial for expanding the specific surface area and pore volume, while sulfuric acid acidification has higher acid strength and produces more acid. The combination of the two at (1.5-2.5):1 takes into account both pore structure development and acid strength enhancement; the total acid concentration of 28%-32% reacts at 105-115℃ for 5-7 hours, which can fully activate the montmorillonite lattice without causing excessive collapse; the solid-liquid ratio of 1:(4-8) ensures sufficient contact between the acid solution and bentonite, resulting in good mass transfer.
[0013] Furthermore, the deep acidification reaction in step (3) is carried out in a reactor with reflux condenser, with a stirring rate of 200-400 rpm. Reflux condenser can prevent the acid from evaporating and being lost above 100°C, maintaining a stable acid concentration; the stirring rate of 200-400 rpm ensures that the bentonite particles are uniformly suspended, avoiding sedimentation that could lead to uneven acidification, while also preventing excessive shear force that could damage the particle morphology.
[0014] Furthermore, the bentonite raw material is calcium-based bentonite or sodium-based bentonite, with a montmorillonite content of not less than 85 wt%; in step (4), the drying temperature is 105℃~120℃, the drying time is 8~12 hours, and the washing is carried out until the pH of the washing solution reaches 6.5~7.5. Montmorillonite is the main mineral for generating active sites through acidification, and its content of not less than 85% is necessary to ensure sufficient acid content; both calcium-based and sodium-based bentonite have typical dioctahedral montmorillonite structures, which can be effectively acidified; drying at 105~120℃ for 8~12 hours can remove physical water and some interlayer water, resulting in a stable structure; washing to pH 6.5~7.5 removes residual acid radicals, avoiding corrosion of subsequent application equipment.
[0015] Furthermore, the complexing isomer obtained by the preparation method has a specific surface area of 300–450 m². 2 / g, with a total acid content of 1.0–1.8 mmol / g; from the particle surface to the core, the Lewis acid density gradually decreases, while the Brønsted acid density gradually increases, with the overall molar ratio of Brønsted acid content to Lewis acid content of the particle being 1:(0.7–1.1). 300–450m 2 The specific surface area of / g provides sufficient reaction sites and adsorption sites; the total acid content of 1.0 to 1.8 mmol / g meets the acid density required for aromatic isomerization catalysis; the B / L molar ratio of 1: (0.7 to 1.1) balances the catalytic function of B acid and the adsorption function of L acid, and the gradient distribution characteristics make the surface layer mainly L acid responsible for impurity interception and the core mainly B acid responsible for catalysis, thus realizing functional zoning in space.
[0016] Furthermore, the pore size distribution of the complexing isomer is concentrated in the range of 3–10 nm, and the pore volume is 0.40–0.65 cm³. 3 / g. The mesoporous pore size of 3–10 nm allows for the free diffusion of base oil hydrocarbon molecules (kinetic diameter <2 nm), while simultaneously creating a sieving effect on macromolecules such as asphaltene (aggregate diameter >10 nm); pore volume 0.40–0.65 cm³. 3 / g ensures sufficient reactant capacity.
[0017] Furthermore, the application of the complexing isomer in the upgrading of regenerated Group I base oil to produce Group II base oil involves mixing the complexing isomer with regenerated Group I base oil at a mass ratio of (5-15):100, and reacting at a reaction temperature of 220℃-280℃, a reaction pressure of 1.0-3.0 MPa, a hydrogen-to-oil volume ratio of (200-500):1, and a space velocity of 0.5-2.0 h⁻¹. -1The complexation isomerization reaction is carried out under the following conditions: A catalyst-to-oil ratio of (5–15):100 ensures sufficient contact between active sites and feedstock; 220–280℃ is the suitable temperature range for Brønsted acid-catalyzed aromatic hydroisomerization; below 220℃, activity is insufficient, and above 280℃, cracking is likely to occur; a hydrogen pressure of 1.0–3.0 MPa inhibits coking and provides a hydrogenation atmosphere, far lower than the 8–15 MPa required for traditional hydroisomerization; a hydrogen-to-oil ratio of 200–500:1 ensures sufficient hydrogen without excessive energy consumption; and a space velocity of 0.5–2.0 h⁻¹. -1 It balances processing capacity and reaction depth.
[0018] Furthermore, the recycled Group I base oil contains no more than 3.0 wt% gum and no more than 200 ppm NMP residue; the upgraded base oil contains no less than 95 wt% saturated hydrocarbons, no more than 3 wt% aromatics, a viscosity index of no less than 105, and NMP residue below the detection limit. Gum ≤ 3.0 wt% and NMP ≤ 200 ppm represent the upper limit of impurity load that the outer shell layer of this catalyst can effectively intercept; exceeding these limits will accelerate adsorption saturation and shorten the product's lifespan. Saturated hydrocarbons ≥ 95%, aromatics ≤ 3%, and VI ≥ 105 correspond to API Group II base oil standards. NMP below the detection limit indicates that the L-acid-rich outer shell layer has a thorough coordination complexation effect on polar NMP, and the product has no risk of solvent residue.
[0019] Furthermore, after 200 hours of continuous operation, the conversion rate of saturated hydrocarbons of the complexing isomer does not decrease by more than 10%. The core-shell structure traps large molecular impurities on the outer layer of the particle, preventing them from entering the internal channels and causing blockage. The active sites of the core Brønsted acid can continuously contact hydrocarbon reactants. Therefore, the activity decay is controlled within 10% within 200 hours, which is a significant improvement in lifespan compared to conventional acidified bentonite (which decays by more than 13% during the same period).
[0020] The beneficial effects of this invention are: (1) Pre-acidification of the surface layer with dilute hydrochloric acid to provide an anchoring basis for the deposition of the outer shell. Dilute hydrochloric acid with a mass concentration of 8% to 15% was used to lightly pre-acidify 200 to 400 mesh bentonite for 1 to 3 hours at 60℃ to 80℃. The solid-liquid mass ratio was controlled at 1:(3 to 5). Under this condition, the acid solution only dissolves the surface layer of the particles, generating a large number of surface silanol groups (Si-OH) as chemical bonding sites for subsequent alumina layer deposition. At the same time, the internal montmorillonite lattice is kept basically intact, avoiding aluminum ions from penetrating into the core and destroying the gradient structure in subsequent deposition steps.
[0021] (2) Homogeneous hydrolysis of urea leads to in-situ deposition of an aluminum oxide shell, forming a gradient-distributed L-acid-rich surface layer. Pre-acidified bentonite is prepared into a 5%–10% aqueous suspension, aluminum salts and urea are added, and a homogeneous precipitation reaction is carried out at 90℃–98℃ for 4–8 hours. Urea slowly decomposes, releasing OH-. - , making Al 3+A thin layer of aluminum oxyhydrate is deposited on the particle surface, with aluminum content decreasing from the surface inwards. This outer shell is rich in coordinated unsaturated Al. 3+ These are Lewis acid sites, which can preferentially complex and adsorb large polar impurities such as N-methylpyrrolidone, colloids, and asphaltenes through coordination, forming an impurity interception barrier on the outer layer of the particles.
[0022] (3) Deep acidification with a hydrochloric acid-sulfuric acid mixture produces high-density Brønsted acid in the core and simultaneously strengthens L-acid in the shell. Prepare a hydrochloric acid-sulfuric acid mixture at a volume ratio of (1-3):1, with a total mass concentration of 25%-35%, and deeply acidify at 100℃-120℃ for 4-8 hours. This step works simultaneously both internally and externally: Al in the montmorillonite octahedral sheets of the core... 3+ Mg 2+ H + Substitution generates numerous Brønsted acid centers in the interlayer, providing catalytically active sites for aromatic hydroisomerization. Simultaneously, the outer aluminum oxide layer is partially etched by the mixed acids, exposing more coordinating unsaturated sites and further increasing the surface Lewis acid density. The synergistic effect of hydrochloric acid and sulfuric acid achieves both specific surface area development and acid strength enhancement, superior to single-acid modification.
[0023] (4) Hydrothermal shaping stabilizes the core-shell interface and enhances structural durability. Hydrothermal treatment at 140℃~160℃ for 2~4 hours causes the alumina layer of the outer shell and the silanols on the surface of the bentonite core to undergo dehydration condensation, forming Si-O-Al chemical bonds. The interfacial bonding force is upgraded from physical adsorption to chemical bonding, and the outer shell is not easy to fall off during the reaction.
[0024] (5) The core-shell functional zones of external adsorption and internal catalysis work synergistically to avoid pore blockage. The high Brønsted acid density of the core is responsible for catalyzing the hydrogenation isomerization of aromatics to saturated cycloalkanes, while the L-acid-rich outer shell is responsible for intercepting and complexing large polar impurities. Large impurities such as colloids and asphaltenes are blocked on the outer layer of the particles and cannot enter the internal pores, causing blockage. The active sites of the core can continue to contact hydrocarbon reactants. Detailed Implementation
[0025] The specific embodiments of the present invention will be described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments.
[0026] Example 1 This embodiment prepares a core-shell structured complex isomer, and the specific steps are as follows: (1) Pre-acidification treatment: Calcium-based bentonite (montmorillonite content 88wt%) was selected as raw material and pulverized until it passed through a 325-mesh standard sieve. 100g of bentonite powder was weighed and added to 400g of 10% dilute hydrochloric acid. The mixture was stirred in a 70℃ water bath for 2 hours at a stirring speed of 250rpm. After the reaction was completed, the mixture was filtered and washed with deionized water until the pH of the filtrate was approximately 5.5. The filter cake was collected to obtain pre-acidified bentonite powder.
[0027] (2) In-situ deposition of aluminum oxide shell: The above-mentioned pre-acidified bentonite powder was dispersed in 1500 mL of deionized water and ultrasonically dispersed for 10 minutes to form a uniform suspension. 18.5 g of aluminum nitrate nonahydrate (approximately 5% of the mass of the pre-acidified bentonite powder based on Al2O3) and 30 g of urea (urea reacts with Al2O3 to form a uniform suspension) were added. 3+ (Molar ratio approximately 8:1), after stirring to dissolve, heat to 95℃ and stir at this temperature for 6 hours. Urea slowly hydrolyzes, releasing OH-. - This process allows aluminum ions to be uniformly deposited on the surface of bentonite particles to form a thin layer of aluminum oxide hydrate, thus obtaining a core-shell precursor slurry.
[0028] (3) Deep acidification with mixed acid: Concentrated hydrochloric acid and concentrated sulfuric acid were added to the above core-shell precursor slurry to adjust the volume ratio of hydrochloric acid to sulfuric acid in the system to 2:1, the total mass concentration of the mixed acid to 30%, and the total solid-liquid mass ratio to approximately 1:6. The mixture was transferred to a reactor with reflux condenser, and stirring was started (300 rpm). The temperature was raised to 110°C for deep acidification reaction for 6 hours to obtain the acidified slurry. During this process, the core bentonite was fully activated to produce a large amount of Brønsted acid, and the outer shell alumina layer was partially etched by acid to form abundant coordinate unsaturated Lewis acid sites.
[0029] (4) Hydrothermal setting and post-treatment: The acidified slurry was transferred to a polytetrafluoroethylene-lined hydrothermal reactor and hydrothermally treated at 150°C for 3 hours to further chemically bond the outer alumina layer with the core bentonite, thus stabilizing the structure. After natural cooling, the product was removed and centrifuged at 3000 rpm for 15 minutes to collect the solid product. It was repeatedly washed with deionized water until the pH of the washing solution was 7.0. The product was dried in a 110°C forced-air drying oven for 10 hours, and after pulverization, the core-shell structured complex isomer was obtained, designated CS-1.
[0030] Example 2 This embodiment prepares a core-shell structured complex isomer with a low aluminum loading. The specific steps are as follows: (1) Pre-acidification: Calcium-based bentonite (88wt% montmorillonite) is crushed to 200 mesh, 3 times the mass of 8% dilute hydrochloric acid is added, and the mixture is reacted at 60℃ for 3 hours. The mixture is then washed until pH≈5.5 to obtain pre-acidified powder.
[0031] (2) Deposition shell: Prepare a 5% suspension, add aluminum nitrate nonahydrate (calculated as 3% of bentonite mass based on Al2O3), urea and Al 3+ The core-shell precursor was obtained by reacting at a molar ratio of 5:1 at 90°C for 8 hours.
[0032] (3) Deep acidification: Add hydrochloric acid-sulfuric acid (volume ratio 1:1), total acid concentration 25%, solid-liquid ratio 1:4, react at 100℃ for 8 hours.
[0033] (4) Hydrothermal setting: hydrothermally heat at 140℃ for 4 hours, wash until pH 6.5, dry at 105℃ for 12 hours to obtain product CS-2.
[0034] Example 3 This embodiment prepares a core-shell structured complex isomer with a high aluminum loading. The specific steps are as follows: (1) Pre-acidification: Sodium-based bentonite (90wt% montmorillonite) is crushed to 400 mesh, 5 times the mass of 15% dilute hydrochloric acid is added, and the mixture is reacted at 80℃ for 1 hour. The mixture is then washed until pH≈5.0 to obtain pre-acidified powder.
[0035] (2) Deposition shell: Prepare a 10% suspension, add aluminum sulfate octahydrate (8% of bentonite mass based on Al2O3), urea and Al 3+ The core-shell precursor was obtained by reacting at a molar ratio of 10:1 at 98°C for 4 hours.
[0036] (3) Deep acidification: Add hydrochloric acid-sulfuric acid (volume ratio 3:1), total acid concentration 35%, solid-liquid ratio 1:8, react at 120℃ for 4 hours.
[0037] (4) Hydrothermal setting: hydrothermally heat at 160℃ for 2 hours, wash until pH 7.5, dry at 120℃ for 8 hours to obtain product CS-3.
[0038] Example 4 This embodiment examines the application effect of core-shell complexing isomers in the upgrading of regenerated Group I base oils.
[0039] Test material: Regenerated Group I base oil (150SN) produced by a waste lubricating oil recycling plant. Main properties: Kinematic viscosity at 40℃ 32.6 mm. 2 / s, kinematic viscosity at 100℃: 5.42 mm³ / s 2 / s, viscosity index 92, flash point 218℃, pour point -12℃, saturated hydrocarbons 86.3wt%, aromatics 11.8wt%, gums 1.9wt%, sulfur 0.085wt%, nitrogen 0.012wt%, NMP residue 128ppm.
[0040] Experimental method: 100 mL of the CS-1 catalyst from Example 1 was loaded into a fixed-bed reactor. Feedstock oil was metered into the reactor. The reaction temperature was 250 °C, the pressure was 2.0 MPa, the hydrogen-to-oil ratio was 300:1, and the volumetric hourly space velocity (VHSV) was 1.0 h⁻¹. -1 Samples were taken after continuous operation stabilized; product number CSP-1.
[0041] Example 5 This example investigates the long-term operational stability of the catalyst. The CS-1 catalyst from Example 1 was used, with the same feedstock as in Example 4. The reaction conditions were: 250°C, 2.0 MPa, hydrogen-to-oil ratio 300:1, and space velocity 1.0 h⁻¹. -1 The system was run continuously for 500 hours, with samples taken every 50 hours to analyze the saturated hydrocarbon content and examine the activity degradation.
[0042] Comparative Example 1 This comparative example directly acidifies calcium-based bentonite in one step using a mixed acid of hydrochloric acid and sulfuric acid (volume ratio 2:1, total concentration 30%), reacting at 110℃ for 6 hours with a solid-liquid ratio of 1:6. After washing and drying, the comparative sample D-1 is obtained.
[0043] Comparative Example 2 In this comparative example, bentonite was first deeply acidified according to the method of Comparative Example 1, and then an equal amount of aluminum nitrate (Al2O3 accounting for 5wt%) was loaded using the equal volume impregnation method. After drying at 120℃, it was calcined at 500℃ for 3 hours to obtain the comparative sample D-2.
[0044] Comparative Example 3 In this comparative example, the bentonite was directly subjected to aluminum oxide deposition and subsequent deep acidification without a pre-acidification step, and the other conditions were the same as in Example 1, resulting in comparative sample D-3.
[0045] Comparative Example 4 In this comparative example, the amount of aluminum salt added was 1% of the mass of bentonite, calculated as Al2O3, and the rest was the same as in Example 1, resulting in comparative sample D-4.
[0046] Comparative Example 5 In this comparative example, the amount of aluminum salt added was 12% of the mass of bentonite, calculated as Al2O3, and the rest was the same as in Example 1, resulting in comparative sample D-5.
[0047] Comparative Example 6 This comparative example uses bentonite acidified with 30% hydrochloric acid, and the rest is the same as in comparative example 1, to obtain comparative sample D-6.
[0048] Comparative Example 7 This comparative example uses commercially available industrial-grade activated clay D-7, with a specific surface area of 185 m². 2 / g, total acidity 0.35mmol / g. Upgraded product DP-7: 86.8% saturated hydrocarbons, with virtually no catalytic isomerization effect.
[0049] Performance testing The performance tests of the embodiments and comparative examples of this invention were conducted according to the following methods: (1) Specific surface area, pore volume and pore size distribution: Nitrogen adsorption-desorption method (BET method) was used for determination. The sample was degassed in vacuum at 300℃ for 4 hours before testing, according to GB / T 19587-2017 "Determination of specific surface area of solid substances by gas adsorption BET method".
[0050] (2) Total acid content and Brønsted acid / Lylene acid molar ratio: determined by pyridine adsorption infrared spectroscopy. After the sample was compressed into tablets, it was dehydrated under vacuum. After the adsorption of pyridine was saturated, it was desorbed at 150℃ and 350℃ respectively. A sample was collected at 1540 cm⁻¹. -1 (Characteristic peak of Brønsted acid) and 1450 cm⁻¹ -1 Calculate the acid content based on the absorbance of the characteristic peak of L acid.
[0051] (3) Content of saturated hydrocarbons, aromatics and gums in base oil: The content of saturated hydrocarbons, aromatics and gums in base oil was determined by column chromatography according to SH / T 0753-2005 "Determination of chemical composition of base oil for lubricating oil (thin layer chromatography)". Silica gel was used as adsorbent and the oil was eluted with n-heptane, toluene and toluene-ethanol in sequence. The mass fraction of each component was calculated by weighing each component.
[0052] (4) Kinematic viscosity and viscosity index: The kinematic viscosity at 40℃ and 100℃ was determined according to GB / T 265-1988 "Determination of kinematic viscosity and calculation of dynamic viscosity of petroleum products", and the viscosity index was calculated according to GB / T 1995-1998 "Calculation of viscosity index of petroleum products".
[0053] (5) NMP residue: determined by gas chromatography.
[0054] (6) Sulfur content: determined according to GB / T 11140-2008 "Determination of sulfur content in petroleum products by wavelength dispersive X-ray fluorescence spectrometry"; nitrogen content was determined according to SH / T 0657-2007 "Determination of trace nitrogen in liquid petroleum hydrocarbons by oxidative combustion and chemiluminescence method".
[0055] (7) Stability evaluation: A fixed-bed continuous reaction device was used, which was operated continuously at constant temperature and pressure. The saturated hydrocarbon content was sampled and analyzed at regular intervals. The rate of decrease in saturated hydrocarbon content was used to characterize the rate of catalyst activity decay.
[0056] Table 1. Comparison of physicochemical properties of complexing isomers in each embodiment and comparative example.
[0057] Table 2 Comparison of main properties of base oils after upgrading in each embodiment and comparative example
[0058] Table 3. Comparison of long-term operational stability of catalysts (changes in saturated hydrocarbon content over operating time)
[0059] Table 4. Economic Comparison of the Invention with Traditional Hydroisomerization Processes
[0060] As shown in Table 1, the specific surface areas of samples CS-1, CS-2, and CS-3 in the three embodiments of the present invention are 396, 328, and 428 m², respectively. 2 The total acid content was 1.42, 1.08, and 1.72 mmol / g, respectively, all higher than the 368 mmol / g of the conventional mixed acid-acidified sample in Comparative Example 1. 2 / g and 1.15mmol / g. CS-3, due to its higher aluminum loading, had an outer shell that contributed additional specific surface area and acidity. In contrast, Comparative Example 2 showed a reduced specific surface area of 325m². 2 / g indicates that the impregnation method causes aluminum salts to enter the pores and cause blockage, which is significantly different from the surface enrichment of the core-shell structure of the present invention.
[0061] Table 2 shows that the feedstock oil contained only 86.3 wt% saturated hydrocarbons and 11.8 wt% aromatics, classifying it as a typical Group I base oil. After treatment with CS-1 according to this invention, saturated hydrocarbons increased to 97.2 wt%, aromatics decreased to 2.0 wt%, the viscosity index rose from 92 to 110, and NMP decreased from 128 ppm to undetectable. All indicators met Group II standards, with some approaching Group II+ levels. CS-2 and CS-3 also met the standards, with CS-3 having the highest total acidity, reaching 97.8 wt% saturated hydrocarbons and only 1.5 wt% aromatics. Comparative Example 1 showed acceptable initial activity with 96.7% saturated hydrocarbons, but its degradation was rapid, as indicated by the stability data in Table 3. Comparative Example 2 showed only 93.8% saturated hydrocarbons, even lower than Comparative Example 1 without aluminum modification, indicating that aluminum salts entering the pores not only did not provide any benefit but also consumed Brønsted acid sites and hindered mass transfer, producing a negative effect. Comparative Example 6 showed only 89.5% saturated hydrocarbons, verifying the synergistic effect of the hydrochloric acid-sulfuric acid mixed acid system. Comparative Example 7 showed that commercially available clay had virtually no catalytic activity and only played a physical adsorption role.
[0062] As can be seen from Table 3, the stability of Comparative Examples 2 and 3 is also inferior to that of the product of this invention. Due to the pore blockage problem, the initial activity of Comparative Example 2 is low and decays rapidly; due to the lack of a pre-acidification step, the shell of Comparative Example 3 is not firmly bonded and gradually falls off during operation, resulting in a gradual loss of impurity interception function, and the saturated hydrocarbon content drops below 90% after 200 hours.
[0063] As shown in Table 4, the process of this invention has significant economic advantages. The reaction pressure is only 1.0–3.0 MPa, far lower than the 8–15 MPa required for hydroisomerization, allowing the use of conventional pressure vessels and significantly reducing equipment investment. The catalyst is a bentonite-based material, costing approximately 3,000 RMB / ton, only about 1.5% of that of precious metal molecular sieve catalysts. Although the single-batch lifespan is shorter than that of precious metal catalysts, considering the price difference of more than 60 times, the catalyst cost per unit processing volume is still significantly lower. Overall, the operating cost of this process is estimated to be approximately 30%–50% of that of traditional hydrogenation processes, demonstrating outstanding economic applicability in small- to medium-scale waste lubricating oil regeneration plants.
[0064] The above-disclosed embodiments are merely a few specific examples of the present invention. However, the embodiments of the present invention are not limited thereto, and any variations that can be conceived by those skilled in the art should fall within the protection scope of the present invention.
Claims
1. A method for preparing a complexing isomerizing agent for the complexation isomerization of regenerated Group I base oil to produce Group II base oil, characterized in that, Includes the following steps: (1) Crush the bentonite raw material to 200-400 mesh, add it to dilute hydrochloric acid with a mass concentration of 8%-15%, with a solid-liquid mass ratio of 1:(3-5), stir and react at 60℃-80℃ for 1-3 hours, and obtain pre-acidified bentonite powder after filtration and washing. (2) Disperse the pre-acidified bentonite powder in deionized water to prepare a suspension with a mass fraction of 5% to 10%, add aluminum salt and urea, heat to 90℃ to 98℃ to carry out homogeneous hydrolysis reaction of urea for 4 to 8 hours, and deposit a thin layer of aluminum oxyhydrate on the surface of bentonite particles in situ to obtain core-shell precursor slurry. (3) Add hydrochloric acid and sulfuric acid to the core-shell precursor slurry, adjust the volume ratio of hydrochloric acid to sulfuric acid in the system to (1-3):1, the total mass concentration of the mixed acid to be 25%-35%, and carry out a deep acidification reaction at 100℃-120℃ for 4-8 hours to obtain acidified slurry; (4) The acidified slurry is transferred to a hydrothermal reactor and hydrothermally treated at 140℃~160℃ for 2~4 hours. After cooling, the solid and liquid are separated, the solid product is collected, washed until neutral and then dried to obtain the complexing isomer.
2. The method for preparing a complexing isomerizing agent for the production of Group II base oils from regenerated Group I base oils according to claim 1, characterized in that, In step (2), the aluminum salt is aluminum nitrate nonahydrate or aluminum sulfate octahydrate, and the amount of aluminum salt added is 3% to 8% of the mass of bentonite based on Al2O3; the molar ratio of urea to aluminum salt is (5 to 10):
1.
3. The method for preparing a complexing isomerizing agent for the production of Group II base oils from regenerated Group I base oils according to claim 1, characterized in that, In step (3), the volume ratio of hydrochloric acid to sulfuric acid is (1.5~2.5):1, the total mass concentration of the mixed acid is 28%~32%, the deep acidification reaction temperature is 105℃~115℃, the reaction time is 5~7 hours, and the total solid-liquid mass ratio of the system after acid addition is 1:(4~8).
4. The method for preparing a complexing isomerizing agent for the production of Group II base oils from regenerated Group I base oils according to claim 1, characterized in that, In step (3), the deep acidification reaction is carried out in a reactor with reflux condenser and the stirring rate is 200-400 rpm.
5. The method for preparing a complexing isomerizing agent for the production of Group II base oils from regenerated Group I base oils according to claim 1, characterized in that, The bentonite raw material is calcium-based bentonite or sodium-based bentonite, and its montmorillonite content is not less than 85 wt%; in step (4), the drying temperature is 105℃~120℃, the drying time is 8~12 hours, and the washing is until neutral when the pH value of the washing liquid reaches 6.5~7.
5.
6. The method for preparing a complexing isomerizing agent for the production of Group II base oils from regenerated Group I base oils according to claim 1, characterized in that, The specific surface area of the complex isomer prepared by the method is 300-450 m². 2 / g, the total acid content is 1.0 to 1.8 mmol / g; from the surface of the particle to the core, the Lewis acid density gradually decreases and the Brønsted acid density gradually increases, and the molar ratio of the overall Brønsted acid content to the Lewis acid content of the particle is 1:(0.7 to 1.1).
7. The method for preparing a complexing isomerizing agent for the production of Group II base oils from regenerated Group I base oils according to claim 6, characterized in that, The pore size distribution of the complexing isomer is concentrated in the range of 3–10 nm, and the pore volume is 0.40–0.65 cm³. 3 / g.
8. The method for preparing a complexing isomerizing agent for the production of Group II base oils from regenerated Group I base oils according to claim 6, characterized in that, The complexing isomer is used in the upgrading of recycled Group I base oil to produce Group II base oil. The complexing isomer is mixed with recycled Group I base oil at a mass ratio of (5–15):100, and the mixture is reacted at a temperature of 220–280°C, a pressure of 1.0–3.0 MPa, a hydrogen-to-oil volume ratio of (200–500):1, and a space velocity of 0.5–2.0 h⁻¹. -1 Complexation isomerization reaction is carried out under certain conditions.
9. The method for preparing a complexing isomerizing agent for the production of Group II base oils from regenerated Group I base oils according to claim 8, characterized in that, The recycled Group I base oil has a gum content of no more than 3.0 wt% and an NMP residue of no more than 200 ppm; the upgraded base oil has a saturated hydrocarbon content of no less than 95 wt%, an aromatic hydrocarbon content of no more than 3 wt%, a viscosity index of no less than 105, and an NMP residue below the detection limit.
10. The method for preparing a complexing isomerizing agent for the production of Group II base oils from regenerated Group I base oils according to claim 8, characterized in that, After the complexing isomer has been running continuously for 200 hours, the saturated hydrocarbon conversion rate decreases by no more than 10%.
Citation Information
Patent Citations
Method for regenerating waste lubricating oil
CN104830515A
Improved production of heavy API group ii base oil
CN108473881A